Heteromeric channel formation and Ca(2+)-free media reduce the toxic effect of the weaver Kir 3.2 allele. - Tucker, S; Pessia, M; Moorhouse, A; Gribble, F; Ashcroft, F; Maylie, J; Adelman, J (1996)
Weaver mice have a severe hypoplasia of the cerebellum with an almost complete loss of the midline granule cells. Recent genetic studies of weaver mice have identified a mutation resulting in an amino acid substitution (G156S) in the pore of the inwardly rectifying potassium channel subunit Kir 3.2. When expressed in Xenopus oocytes the weaver mutation alters channel selectivity from a potassium-selective to a nonspecific cation-selective pore. In this study we confirm by cell-attached patch-clamp recording that the mutation produces a non-selective cation channel. We also demonstrate that the cell death induced by weaver expression may be prevented by elimination of calcium from the extracellular solution as well as by coexpression with the wild-type Kir 3.2 allele, or other members of the Kir 3.0 subfamily. These results suggest that the weaver defect in Kir 3.2 may cause cerebellar cell death by cell swelling and calcium overload. Cells which express the weaver subunit, but which normally survive, may do so because of heteromeric subunit assembly with wild-type subunits of the Kir 3.0 subfamily.